2016
DOI: 10.1093/jisesa/iew060
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Niche Partitioning ofEuphaea formosaandMatrona cyanoptera(Odonata: Zygoptera) on the Basis of DNA Barcoding of Larval Feces

Abstract: Odonate larvae are commonly considered opportunistic general predators in freshwater ecosystems. However, the dietary breadth of most odonate larvae in forest streams is still poorly documented. We characterized the prey species and estimated the level of dietary niche overlap of two damselflies, Euphaea formosa Hagen 1869 and Matrona cyanoptera Hämäläinen and Yeh, 2000 in a forest stream of central Taiwan on the basis of DNA barcoding of larval feces. A collection of 23 successfully identified cytochrome c ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…The strategy used to characterize and compare the taxonomic diversity of the diets can also determine the results. Most studies treat taxa or OTUs as discrete independent components, rather than phylogenetically correlated elements (e.g., Arrizabalaga-Escudero et al, 2018;Cheng & Lin, 2016;Kartzinel et al, 2015). This entails losing large part of the taxonomic information molecular diet studies provide.…”
Section: Taxonomic Assignmentmentioning
confidence: 99%
“…The strategy used to characterize and compare the taxonomic diversity of the diets can also determine the results. Most studies treat taxa or OTUs as discrete independent components, rather than phylogenetically correlated elements (e.g., Arrizabalaga-Escudero et al, 2018;Cheng & Lin, 2016;Kartzinel et al, 2015). This entails losing large part of the taxonomic information molecular diet studies provide.…”
Section: Taxonomic Assignmentmentioning
confidence: 99%
“…Whilst DNA metabarcoding may more clearly determine which species are represented in mixed samples, metabarcoding methods are relatively costly and require more specialist equipment, which may not be available to many wildlife managers. In this study, PCR and Sanger sequencing reliably identified the predator of origin for 86% of scat samples, which is likely to be sufficient for many management applications and is a higher success rate than has been reported for several other faecal DNA studies (e.g., [ 41 ], where 79% of sequences were amplified using a 134-bp fragment, and [ 56 ], where <70% of sequences were amplified using regions ranging from 243 bp to 708 bp according to target taxon). Using our mini-barcode, DNA can be screened for the presence of multiple Australian predator species in a single and inexpensive test, without the need to develop and apply a set of species-specific primers for each predator of interest.…”
Section: Discussionmentioning
confidence: 61%
“…less than 900 s did not allow for sexing), despite their frequent use (Perron et al, 1972. This work therefore leads to new possibilities for insect anesthesia, when killing the insect target is often undesirable (Oi et al, 2013;Price et al, 2015;Cheng & Lin, 2016;Sikulu-Lord et al, 2016). Other than the effects on survival, other potential sub-lethal effects of TEA were not investigated in this study, whereas these effects have been thoroughly investigated with the other two anesthesia techniques.…”
Section: Discussionmentioning
confidence: 99%